Chronic Eosinophilic Leukemia—Not Otherwise Specified (NOS) in the Background of a Large Cell Lymphoma - Wilson I. Gonsalves; Rong He; Animesh Pardanani; Vinay Gupta; Jacob P. Smeltzer; Curtis A. Hanson; Thomas E. Witzig (Case Reports in Hematology)
Clonal eosinophilic disorders are rare among hematological malignancies. Most eosinophilia tends to be due to secondary causes such as infections, hypersensitivity conditions, drug reactions, and connective tissue disorders. The presence of a primary clonal eosinophilic disorder such as chronic eosinophilic leukemia—not otherwise specified (NOS) in the presence of a synchronous large cell lymphoma—is rare making the diagnosis challenging. We present a case of a 51-year-old female with the aforementioned presentation and demonstrate the extensive workup performed to identify the diagnosis.